All Days 2009
DOI: 10.2523/iptc-13266-ms
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Asphaltene Behavior for Gas Injection Risk Analysis

Abstract: Asphaltene study is now becoming a regular menu as a part of gas injection studies 1–11. The asphaltene onset pressure (AOP) is one of the most important factors to understand asphaltene precipitating behavior. The SDS (solid detection system) based on light scattering technique has been quite popular and widely used in all over the world 1,7–9,12–15. The simple experiments to measure AOP are usually conducted using mixture of reservoir fluid and injection gas, and various gas mixing volume are assumed to be i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Gonzales et al (2005) showed that the effect of CO 2 and ethane on AOP is weaker than methane [39]. Yonebayashi et al (2011) claimed that enriched gas has no effect on the upper AOP; however, it would decrease the lower AOP [40]. In this work, the effect of different gases in term of asphaltene onset pressure is investigated to achieve a comprehensive understanding about it and help to choose the best EOR method.…”
Section: Introductionmentioning
confidence: 91%
“…Gonzales et al (2005) showed that the effect of CO 2 and ethane on AOP is weaker than methane [39]. Yonebayashi et al (2011) claimed that enriched gas has no effect on the upper AOP; however, it would decrease the lower AOP [40]. In this work, the effect of different gases in term of asphaltene onset pressure is investigated to achieve a comprehensive understanding about it and help to choose the best EOR method.…”
Section: Introductionmentioning
confidence: 91%
“…Nitrogen injection is being evaluated as a way to accelerate and increase oil recovery, through an improvement of the gravity drainage, main producing mechanism in this reservoir, and by pressure maintenance purposes, Arevalo-V, et al 1996 [13]. During the gas injection process, the injected gas composition is changed due to the vaporizing gas drive (VGD) mechanism, in which gas is enriched with intermediate molecular weight hydrocarbons from reservoir oil Yonebayashi et al, 2009 [14].…”
Section: Introductionmentioning
confidence: 99%